1965
DOI: 10.2172/4538819
|View full text |Cite
|
Sign up to set email alerts
|

Brookhaven National Laboratory Process for the Continuous Conversion of High-Level Radioactive Waste to Phosphate Glass

Abstract: The conversion of high-level radioactive wastes to-phosphate glass offers a promising means of incorporating fission products in stable media suitable for ultimate disposal. In the Brookhaven process, phosphoric acid is added to the aqueous waste and the solution converted.to phosphate glass in•r~ continuous operation upon raising the temperature in two steps to ll00°C-l200°C. The process has be~n tested on a pilot plant scale for some 3000 hours. The report presents the results of the Brookhaven. investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Phosphate glasses have some advantages over borosilicate glasses, such as a lower melting temperature and higher solubility for problematic elements, such as sulfur, and were investigated as early as the 1960s (Clark et al 1966, Tuthill et al 1966. Later work on sodium-aluminum phosphate glass (van Geel 1976) and iron-aluminum phosphate glass (Grambow and Lutze 1980) showed that some of these glasses had comparable or better chemical durability than the borosilicate glasses.…”
Section: Phosphate Glassesmentioning
confidence: 99%
“…Phosphate glasses have some advantages over borosilicate glasses, such as a lower melting temperature and higher solubility for problematic elements, such as sulfur, and were investigated as early as the 1960s (Clark et al 1966, Tuthill et al 1966. Later work on sodium-aluminum phosphate glass (van Geel 1976) and iron-aluminum phosphate glass (Grambow and Lutze 1980) showed that some of these glasses had comparable or better chemical durability than the borosilicate glasses.…”
Section: Phosphate Glassesmentioning
confidence: 99%
“…|tJ|olecular sieves are unique among industrial adsorbents in their ability to separate molecules on the basis of molecular size. Recent applications (2,3,5,7) in separating and purifying gases and liquids have placed molecular sieve adsorption processes among the major separation operations used in some process industries.…”
Section: Discussionmentioning
confidence: 99%